2013
DOI: 10.3329/bjnut.v24i0.14041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Socio-economic, Demographic and Internet Exposure Factors on School Performance among Selected Students of Nilkhet High School

Abstract: Abstract:A cross sectional study was carried out to investigate the effects of socio-economic, demographic and internet exposure factors on school performance among 10 grade students of Nilkhet High School. All of the eighty seven students were selected for this study. In this study school performance was measured by class roll number. The lower the class roll number the better the school performance. During Chisquare test grade (A+, A, A-, B, C, D) achieved in the class 9 final examination was taken as depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…Although the frequency of using different SNSs is well documented in the literature (See Asad, et al, 2012;Chen, & Bryer, 2012;Gonzalez, 2009;Hampton et al, 2011;Lenhart, 2009;Mafiz, Ismail and Bhuyan, 2011;Pew, 2009;Rainie, 2011), none of the aforesaid studies and other previous studies have assessed the quantity of active SNSs that each student may have and its association with that student's academic results. Besides, impacts of both, the quantity of installed mobile messaging applications and its frequency of use, on students' academic results have not been explored yet in Bangladesh.…”
Section: Research Gapmentioning
confidence: 98%
See 4 more Smart Citations
“…Although the frequency of using different SNSs is well documented in the literature (See Asad, et al, 2012;Chen, & Bryer, 2012;Gonzalez, 2009;Hampton et al, 2011;Lenhart, 2009;Mafiz, Ismail and Bhuyan, 2011;Pew, 2009;Rainie, 2011), none of the aforesaid studies and other previous studies have assessed the quantity of active SNSs that each student may have and its association with that student's academic results. Besides, impacts of both, the quantity of installed mobile messaging applications and its frequency of use, on students' academic results have not been explored yet in Bangladesh.…”
Section: Research Gapmentioning
confidence: 98%
“…However, by utilizing non-parametric statistics (Chi square test), both of these two aforesaid studies have significantly concluded that, (i) the school performance measured by grade of the students was significantly related with the work on internet (Mafiz, Ismail and Bhuyan, 2011), and (ii) students' poor performance (lower grades) is one of the negative effects of using SNSs (Asad, et al, 2012).…”
Section: Use Of Snss In the Academic Sector Of Bangladeshmentioning
confidence: 99%
See 3 more Smart Citations